Single-Parent Families and In-Work Poverty - Rense Nieuwenhuis; Laurie C. Maldonado (Luxembourg Income Study (LIS), 2017)
Single-parent families face unique challenges when it comes to in-work poverty. Without a second caregiver and earner, single parents have to compete with dual-earner couples for their position in the earnings distribution. Facing precarious employment and gendered wage inequality, single-parent families face a high risk to experience poverty even when they are working. This chapter presents empirical evidence on in-work poverty and inadequate wages in the policy context of 18 OECD countries. The impact of family structure, occupation, regulations of part-time work, paid parental leave, and various redistributive policies are examined. We distinguish three distinct patterns of performance in countries' approach to in-work poverty among single parents: A balanced approach of ensuring low inequality on the labor market combined with redistribution, an unbalanced approach of combating in-work poverty mostly through redistribution, and an approach in which high inequality on the labor market is compensated with redistributive policies only to a very limited extent. Countries that rely on a balanced approach to reduce inequality on the labor market, both with respect to class and gender, combined with an adequate level of redistribution, seem best situated for a durable reduction of poverty among working single parents.
Keywords: 330